2022
DOI: 10.1088/1742-6596/2240/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterization of CuO coatings deposited by reactive magnetron sputtering

Abstract: In this work, CuO coatings were deposited on 304 L stainless steel substrates by reactive magnetron sputtering. During the process, the substrate temperature was varied in the range from 100 °C to 400 °C. The crystallographic structure of the samples thus prepared was characterized by X-ray diffraction, and the results are discussed with respect to the technological conditions applied. It was found that the phase composition of the deposited CuO coatings is in the form of a monoclinic crystal structure. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results showed a significant improvement in the biological response, corrosion resistance, and antibacterial properties of the coated implant material. Our previous study [34] showed the possibility of successful deposition of CuO coatings on stainless steel substrates by reactive magnetron sputtering. The results demonstrated that all coatings are in the form of a monoclinic structure.…”
Section: Of 13mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed a significant improvement in the biological response, corrosion resistance, and antibacterial properties of the coated implant material. Our previous study [34] showed the possibility of successful deposition of CuO coatings on stainless steel substrates by reactive magnetron sputtering. The results demonstrated that all coatings are in the form of a monoclinic structure.…”
Section: Of 13mentioning
confidence: 99%
“…The results demonstrated that all coatings are in the form of a monoclinic structure. The increase in the substrate temperature during the deposition of the coatings was accompanied by a change in the orientation of the crystallites from (022) to (110) and by a decrease in the concentration of imperfections [34].…”
Section: Of 13mentioning
confidence: 99%